Allatotropin Modulates Myostimulatory and Cardioacceleratory Activities in Rhodnius prolixus (Stal) - Villalobos-Sambucaro, María José (2015)
Fil: Villalobos-Sambucaro, María José. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Cátedra Histología y Embriología Animal; Argentina